Epidemiologi Perilaku dan Kesehatan Mental Mahasiswa Urban: Analisis Korelatif Tingkat Stres terhadap Kualitas Tidur Komunitas Akademik di Kota Medan - Juwita Nababan; Meriathi Talambenua; Gemila Hayati (SUAN PUBLISHER, 2026)
Academic pressures and psychosocial transitions in urban higher education environments place students at risk of mental distress. Poorly managed stress directly contributes to circadian rhythm disruption and decreased sleep hygiene. This study aimed to analyze the relationship between stress levels and sleep quality among active university students in Medan. This quantitative study used an observational analytical design using a cross-sectional approach. This study involved 150 active university students in Medan selected using a proportionate stratified random sampling technique. Data collection used a standardized questionnaire, the Perceived Stress Scale (PSS-10) to measure stress levels and the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality. Data were analyzed univariately and bivariately using the Spearman Rank correlation test and cross-table analysis with an Odds Ratio (OR) parameter at a significance level of α = 0.05. The results of the univariate analysis showed that the majority of students experienced moderate (53.3%) and high (26.7%) levels of stress. A sleep quality evaluation revealed that 73.3% of respondents reported poor sleep quality. Bivariate analysis revealed a significant and positive association between stress levels and poor sleep quality in college students (p < 0.001; r = 0.584). Respondents with high stress levels were 4.8 times more likely to experience poor sleep quality compared to those with low stress levels (OR = 4.82; 95% CI = 2.15 - 10.81). High stress levels are strongly correlated with decreased sleep quality among college students in Medan. The development of an integrated early detection system for mental health and preventive health promotion services within the campus environment is needed.